Production potential of early segregated all-male population of Macrobrachium rosenbergii (de Man) in tropical earthen pond condition - Suresh Babu, P P; Venugopal, G; Reddy, A K (Indian Journal of Fisheries, 2016)
Production potential of all-male culture of Macrobrachium rosenbergii was evaluated by comparing the yield obtained from an early segregated all-male population (post-larvae of average size â‰… 50 mm) with a mixed population comprising males and females in 1:1 ratio. Nursery reared prawns were size graded, sexes segregated manually by observing the presence or absence of appendix masculina, stocked in four replicates in earthen ponds of 200 m2 area at a density of 1 m-2 and reared for a period of 90 days. The results revealed an all-male population production of 30.7 g m-2 90 days-1 with an average individual weight of 42.2 g with 62.3% of marketable prawns whereas in mixed population, a production of 23.65 g m-2 90 days-1 with an average individual weight of 30.7 g with 47.14% of marketable prawns were obtained. The production of all-male population was 30% higher than that of mixed population.